2004
DOI: 10.1007/s00251-004-0675-0
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic discovery and initial characterisation of nine novel antimicrobial peptide genes in the chicken

Abstract: Antimicrobial peptides (AMPs) are essential components of innate immunity in a range of species fromDrosophila to humans and are generally thought to act by disrupting the membrane integrity of microbes. In order to discover novel AMPs in the chicken, we have implemented a bioinformatic approach that involves the clustering of more than 420,000 chicken expressed sequence tags (ESTs). Similarity searching of proteinspredicted to be encoded by these EST clusters-for homology to known AMPs has resulted in the in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
188
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(204 citation statements)
references
References 41 publications
12
188
1
3
Order By: Relevance
“…All of these cathelicidin genes have four exons, except for chCATH-2, which has an additional exon, Ib, that is predicted to be incapable of encoding functional protein products (data not shown). The three chicken cathelicidin relatives of mammalian cathelicidins have been identified recently by other investigators on the basis of sequence similarity and antimicrobial activity (24)(25)(26) and have been given the names fowlicidin 1, 2, and 3 (26).…”
Section: Resultsmentioning
confidence: 99%
“…All of these cathelicidin genes have four exons, except for chCATH-2, which has an additional exon, Ib, that is predicted to be incapable of encoding functional protein products (data not shown). The three chicken cathelicidin relatives of mammalian cathelicidins have been identified recently by other investigators on the basis of sequence similarity and antimicrobial activity (24)(25)(26) and have been given the names fowlicidin 1, 2, and 3 (26).…”
Section: Resultsmentioning
confidence: 99%
“…High to medium levels of expression of the cathelicidin-1 were described from the crop to the small and large intestines of chickens. The liver levels of cathelicidin-1 were low and those of the cathelicidin-2 were higher (Lynn et al, 2004;van Dijk et al, 2005). Their activity against Gram-positive and Gramnegative microorganisms and also against pathogenic fungi and nematodes has been demonstrated (Scocchi et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Cathelicidins are antimicrobial peptides and expression of four cathelicidins was described in poultry so far (Lynn et al, 2004;van Dijk et al, 2005;. These are the cathelicidin-1 or fowlicidin-1 (Lynn et al, 2004), chicken myeloid antimicrobial peptide 27 (CMAP27) or fowlicidin-2 (van Dijk et al, 2005), third chicken cathelicidin fowlicidin-3 (Xiao et al, 2006) and cathelicidin-B1 (Goitsuka et al, 2007). Cathelicidins were found predominantly in epithelial cells in the gastrointestinal tract and kidney, and in myeloid tissue (Sang & Blecha, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An NJ tree at amino acid level and the respective nucleotide alignment were both used in the CODEML and CODEMLSITES analyses according to Lynn et al (2004aLynn et al ( , 2004b; details of the exact methods for these analyses are found in Zambounis et al (2012). Briefly, the amino acid sequence alignment was conducted by employing the MUSCLE software (Edgar 2004), whilst the construction of the respective phylogenetic tree was performed using the MEGA 5 software (Tamura et al 2011).…”
Section: P Monticola Tir-nbs-lrr Rgas Evolutionary Analysismentioning
confidence: 99%